2018
DOI: 10.1177/0300060518760463
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour blood pressure variability plays a detrimental role in the neurological outcome of hemorrhagic stroke

Abstract: BackgroundBlood pressure variability (BPV) is a modifiable risk factor for stroke. This study was performed to determine the prognostic role of BPV in patients with acute hemorrhagic stroke.MethodsThe data of 131 hospitalized hypertensive patients with spontaneous intracerebral hemorrhage (sICH) were collected. All patients underwent examinations using several neurological scales (Glasgow Coma Scale, National Institutes of Health Stroke Scale, and modified Rankin scale [mRS]) and BP measurements at different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The multivariate logistic regression analysis was accomplished for the proper time for control of blood pressure showed that diastolic blood pressure 1 h after admission, systolic BP 6 h after admission, and systolic blood pressure 24 h after admission were accompanied by the favorable outcome. Similarly, Huan-Xin et al 2018 concluded that high systolic or diastolic blood pressure during 24 h ICH onset is accompanied by the 90-day neurological outcome, and the first 24-h BP plays a critical role in the neurological outcome of hemorrhagic stroke [37]. Also, the second Intensive Blood Pressure Reduction in the Acute Cerebral Hemorrhage Trial (INTERACT2) assessed the predictive value of BP variability in outcomes for ICH patients (within 6 h after symptom onset) targeting BP levels to lower than 140 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate logistic regression analysis was accomplished for the proper time for control of blood pressure showed that diastolic blood pressure 1 h after admission, systolic BP 6 h after admission, and systolic blood pressure 24 h after admission were accompanied by the favorable outcome. Similarly, Huan-Xin et al 2018 concluded that high systolic or diastolic blood pressure during 24 h ICH onset is accompanied by the 90-day neurological outcome, and the first 24-h BP plays a critical role in the neurological outcome of hemorrhagic stroke [37]. Also, the second Intensive Blood Pressure Reduction in the Acute Cerebral Hemorrhage Trial (INTERACT2) assessed the predictive value of BP variability in outcomes for ICH patients (within 6 h after symptom onset) targeting BP levels to lower than 140 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional craniotomy for hematoma removal plus bone flap decompression is commonly used for patients with large volume hematoma. Previous studies demonstrated that it could reduce the intracranial pressure, prevent and reduce blood cell decomposition after bleeding, increase the survival rate, and improve the quality of life [ 29 , 30 ]. However, iatrogenic injuries of conventional open surgery remain serious.…”
Section: Discussionmentioning
confidence: 99%
“…Manning et al's 26 systematic review reflected similar results, with greater systolic BPV following IVT for AIS being associated with poor long‐term functional outcome. Similarly, BPV‐specific cohort studies and post‐hoc analysis of previous randomized controlled trials have shown that short‐term BPV in patients with intracerebral hemorrhage is strongly associated with hematoma expansion, neurological deterioration, and poor functional outcome at 3 months 27‐29 …”
Section: Discussionmentioning
confidence: 95%